Evaluation studies on the combined effect of hydrothermal treatment and octenyl succinylation on the physic-chemical, structural and digestibility characteristics of sweet potato starch - Lv, Qing-Qing; Li, Gao-Yang; Xie, Qiu-Tao; Zhang, Bao; Li, Xiao-Min; Pan, Yi; Chen, Han-Qing (Food chemistry, 2018)
•The HOSA-SPS with different DS was prepared by prior modification with HMT.•The DS of HOSA-SPS was higher than that of OSA-SPS in the same reaction condition.•HMT resulted in a crystalline transformation from C- to A-type.•The To, Tp, Tc and ΔH of OSA-8 and HOSA-8 were lower than those of NSPS and HSPS, respectively. In order to increase the degree of substitution (DS), a combination of heat-moisture treatment (HMT) and octenyl succinylation (OSA) was used to modify sweet potato starch (SPS). The content of OSA had significant influence on the DS of starch, and DS of HMT OSA-modified SPS (HOSA-SPS) was higher than that of OSA-modified SPS (OSA-SPS), indicating that prior HMT could enhance the reaction. HOSA-SPS showed higher contents of SDS and RS in comparison with OSA-SPS as OSA concentration was beyond 6%. HMT decreased swelling power of starch while OSA modification had a contrary role (p < 0.05). Scanning electron microscopy (SEM) showed starch was destroyed by OSA modification while HMT had slight effect on the structure. X-ray diffraction (XRD) indicated that crystal type of starch was transformed from C- to A-type resulted from HMT, and remained unchanged by OSA modification. The onset, peak, and conclusion gelatinization temperatures of starch increased by HMT and decreased by OSA modification (p < 0.05).